The Effect of Gabapentin on Oogenesis and Gonadotropic Female Sex Hormones in Adult Female Mice - Akbar Karimi; Elham Etemadi; Setayesh Keshavarzi (مجله دانشکده پزشکی اصفهان, 2019)
Background: Gabapentin, in addition to being an antiepileptic drug, also works against neuropathic pain. Despite the different therapeutic effects of gabapentin, no study has been performed on its effects on the process of oogenesis and female sex hormones. This study was performed to assess the effect of gabapentin on oogenesis and gonadotropic female sex hormones in adult female mice.